Low Tide at Pourville, near Dieppe, 1882 - Claude Monet (Wikimedia Commons, 1882)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Low Tide at Pourville, near Dieppe, 1882.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons